DETERMINAN MINAT DALAM MENYUSUN LAPORAN KEUANGAN UMKM DI PASAR KLEWER SURAKARTA - Fransisca Sekar Ayu Putri; Astuning Saharsini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the factors that influence the interest of MSME actors in preparing MSME financial statements. This study used primary data obtained through the distribution of questionnaires with Likert scale measurement techniques. The population of this study is all MSME players in the Klewer Market as many as 2,215 actors with samples selected using the puposive sampling method by applying the slovin formula which produces as many as 96 MSMEs. In this study, instrument tests were carried out with validity tests and reliability tests, classical assumption tests with normality, multicollinearity and heteroscedasticity tests, multiple regression tests, and hypothesis tests with f tests and t tests. The result of this study is that the use of technology and educational background have a positive effect on interest in compiling MSME financial statements in the Surakarta Klewer Market while business scale, socialization and business age do not affect interest in compiling MSME financial statements in the Surakarta Klewer Market.